The effects of melatonin on focal cerebral ischemia-reperfusion model - Kavakli, A; Sahna, E; Parlakpinar, H; Yahsi, S; Ogeturk, M; Acet, A (Saudi Med J, 2004)
[Abstract Not Available]
Keywords: Artery Occlusion; Rats; Stroke